2018
DOI: 10.21467/ias.5.1.1-11
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Herbs for Improving the Quality of Life

Abstract: A B S T R A C TIn the world, there are many systems of traditional medicine. Cancer is the major public health burden both in developing and developed countries. Around 50% of existing medicines for cancer treatment have plants origin. Anticancer property of some plant extracts proven to be significantly effective in the treatment of cancer. Many herbs like sadabahar, turmeric, Kalonji, cannabis, garlic, flaxseed contain active components which may be effective in prevention and treatment of many cancers. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 73 publications
0
2
0
3
Order By: Relevance
“…An analysis of turmeric simplicial powder's chemical composition revealed that its primary components were curcuminoid chemicals, fatty oils, and essential oils. Chemical analyses of different turmeric simplicial revealed that the chemical composition of the turmeric plant was 60-70 percent curcuminoid chemicals, 4.2 to 14 percent essential oil, and 4.4 to 12.7 percent fatty oil [45][46][47]. Three curcuminoid chemicals make up the bulk of turmeric: Curcumin, also known as 1,7-bis(4-hydroxy-3-methoxyphenyl)-1,6heptadiene-3,6-dione, is a compound with a number of biological functions.…”
Section: The Substances Found In Turmericmentioning
confidence: 99%
See 1 more Smart Citation
“…An analysis of turmeric simplicial powder's chemical composition revealed that its primary components were curcuminoid chemicals, fatty oils, and essential oils. Chemical analyses of different turmeric simplicial revealed that the chemical composition of the turmeric plant was 60-70 percent curcuminoid chemicals, 4.2 to 14 percent essential oil, and 4.4 to 12.7 percent fatty oil [45][46][47]. Three curcuminoid chemicals make up the bulk of turmeric: Curcumin, also known as 1,7-bis(4-hydroxy-3-methoxyphenyl)-1,6heptadiene-3,6-dione, is a compound with a number of biological functions.…”
Section: The Substances Found In Turmericmentioning
confidence: 99%
“…Called propenoate or 1,7-bis calebin A (4hydroxy-3-methoxyphenyl) -\s1,4,6-heptatriene-3-one,1hydroxy-1,7-bis(4hydroxyphenyl)-3-methoxyphenyl) the 3.5dione of 1,7-bis-6 heptene (4-hydroxyphenyl) 1,7-bis (1heptene-3,5-diones), 1,5-bis (1,4,6-heptatriene-3-ones), and 1,4-hydroxyphenyl (1,7) (4-hydroxy-3-methoxyphenyl) -1,4pentadiene-3-on [49]. Curcuminone and dehydrocurdion were also found in the MeOH extract of the turmeric rhizome, in addition to curcuminoids (4S,5S) Some of the substances that are found in turmeric include curcumenol, isoprocurcumenol, zedoaronediol, procurcumenol, epiprocurcumenol, germacron-13-al, bisabola-3,10-diene-2-one, bisabola-3,10diene, bisacumol, bisacurone, 4-hydroxy-bisabola-2,10-diene-9-one, and procurcuma [50]. The three distinct curcuminoid compounds are curcumin, demethoxycurcumin, and bisdemethoxycurcumin [51].…”
Section: The Substances Found In Turmericmentioning
confidence: 99%
“…Selain tanaman jahe, menurut hasil studi kimia dalam tanaman kunyit terdapat kandungan senyawa yang berfungsi sebagai antioksidan, antiinflamasi, antitumor, antivirus dan juga menguatkan sistem kekebalan tubuh pada manusia (Qaiser et al, 2018). Hal ini juga menjadi daya tarik minat masyarakat kelas menengah dalam mengonsumsi tanaman kunyit.…”
Section: Keterlibatanunclassified
“…Kunyit merupakan bagian tanaman yang popular di Indonesia yang digunakan dalam pembuatan obat-obatan dan jamu. Dimana kandungan senyawa metabolit sekunder yang dimiliki tanaman kunyit ini memiliki fungsi sebagai antioksidan, antiinflamasi, antitumor, antivirus, dan juga untuk memperkuat sistem imun (Qaiser, et al, 2018). Kunyit mengandung senyawa kurkumin yang dikenal sebagai imunomodulator.…”
Section: Tabel 2 Distribusiunclassified